FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM MENANGANI KRISIS PANGAN DI SURIAH TAHUN 2011-2015 - Muhammad Guspi; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This reseach explain about role of internastional organization FAO on getting into a scrabe food crisis disaster. This reseach using a descriptive to explain about food in Syria. According Maflecroft report Syria as become the first country getting into trouble food insecurity. It is certainly impact to food sovereignity soit will effecting on food crisis. Syria food crisis is twothings. First, situation of Syrian conflict seemed to be an endless war. Second, global climate change on 2006 have been effecting to flood and dryness. It caused Syria have ekstrim climate change, mountain range and bad irrigation. This study use the qualitative research methode with library reseach. The sources of data are from the journals, books and the internet sites. This study uses the role international organization theory and non-state level of analysis. The reseach shows that Food and Agriculture Organization (FAO) has an important role in handling of food crisis in Syria with an implementation program. Keywords, Food and Agriculture Organization, Food Crisis, conflict, global change.